2007
DOI: 10.1177/0013164406294777
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Robustness of Recent Methods for Analyzing Multivariate Repeated Measures Designs

Abstract: This study evaluated the robustness of two recent methods for analyzing multivariate repeated measures when the assumptions of covariance homogeneity and multivariate normality are violated. Specifically, the authors' work compares the performance of the modified Brown-Forsythe (MBF) procedure and the mixed-model procedure adjusted by the Kenward-Roger solution available in SAS PROC MIXED. The authors found that, overall, the MBF procedure appeared to be the least sensitive to the factors examined in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…In the specific context of univariate factorial designs, previous studies had revealed that the two procedures were generally robust to violations of underlying assumptions (Keselman, Carriere, & Lix, 1995;Vallejo et al, 2010a, b). On the other hand, MBF and MLM have also been proven to be robust when they have been used to analyze longitudinal data with unequal dispersion matrices (Vallejo & Ato, 2006;Vallejo et al, 2007). Our results are consistent with those obtained in the aforementioned studies; furthermore, they provide new findings that help researchers in the selection of feasible alternatives for testing main and interaction effects.…”
Section: Discussion and Recommendationssupporting
confidence: 89%
See 2 more Smart Citations
“…In the specific context of univariate factorial designs, previous studies had revealed that the two procedures were generally robust to violations of underlying assumptions (Keselman, Carriere, & Lix, 1995;Vallejo et al, 2010a, b). On the other hand, MBF and MLM have also been proven to be robust when they have been used to analyze longitudinal data with unequal dispersion matrices (Vallejo & Ato, 2006;Vallejo et al, 2007). Our results are consistent with those obtained in the aforementioned studies; furthermore, they provide new findings that help researchers in the selection of feasible alternatives for testing main and interaction effects.…”
Section: Discussion and Recommendationssupporting
confidence: 89%
“…Although a number of estimation strategies are available, the present article uses REML estimation as implemented through the SAS Institute's (2008) PROC MIXED program. Following Vallejo et al (2007), the multivariate linear model (hereafter referred to as MLM) described in Eq. 1 can be fitted using PROC MIXED by stacking the p nvectors y i into a single np × 1 vector e y; the p q-vectors β i into a pq × 1 vector e β; and the p n-vectors e i into a np × 1 vector e e: The resultant vector form can be written as…”
Section: Multivariate Version Of the General Linear Model (Mlm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Data were generated using SAS/IML (version 9.4), since this software is one of the most suitable for simulating data (Kashyap, Butt, & Bhattacharjee, 2009) and is also one of the most popular for implementing the Vale and Maurelli method (Keselman & Lix, 1997;Lix et al, 2003;Vallejo, Arnau, & Ato, 2007;Vallejo & Livacic-Rojas, 2005).…”
Section: A Monte Carlo Studymentioning
confidence: 99%
“…In several simulation studies of repeated measures designs, the distributions were classified as either normal or slightly, moderately, or strongly biased distributions (Berkovits, Hancock, & Nevitt, 2000;Vallejo et al, 2007). Among the strongly biased distributions, a number of simulation studies have analyzed the log-normal distribution Keselman, Kowalchuk, & Boik, 2000;and Kowalchuk et al, 2004, among others).…”
Section: Study Variablesmentioning
confidence: 99%